Data Leakage of the Indonesian Elections Commission in Legal Aspects of Personal Data Protection - utama, Frendika suda; Purwoleksono, Didik Endro; Rachman, Taufik (Media Iuris, 2024)
Hackers illegally accessed the Indonesian General Elections Commission’s (KPU) voter data system to collect voter data to sell to third parties. The regulation requires accountability for voter data leakage to protect people’s privacy rights in Indonesia’s personal data protection concept. Legal analysis of the modus operandi of personal data sales cases results in patterns of information system vulnerabilities, which can then be used to prevent personal data leakage and improve voter data protection in Indonesian elections. One of the reasons for passing the personal data protection law is the rampant cases of confidential data leakage that occur in government and private institutions in Indonesia. Hackers of voter data systems aim to profit from personal data sold to third parties. The role of the cybersecurity task force team needs to be improved with more concrete arrangements in law enforcement, and mitigating voter data leakage can provide legitimacy for the implementation of credible, reliable, and professional elections in Indonesia. Establishing the task force will optimize the application of voter data systems in conducting general elections in Indonesia and improve personal data protection.